(untitled) (Research, Society and Development, 2023)
Objective: to highlight the insertion of health literacy in nursing based on productions linked to Stricto sensu postgraduate programs. Method: systematic narrative review of theses and dissertations in the area of nursing, based on the CAPES theses and dissertations database and the IBICT Brazilian digital library of theses and dissertations. Results: 46 productions were selected, the first published in 2012 and continuing until 2022, 63% occurred in the last three years, 28% are from the Postgraduate Program in Nursing at the Universidade Federal de Goiás, 76% had one of the objectives of scaling the health literacy, for this, the most used instruments were: Health Literacy Questionnaire, Short Test of Functional Health Literacy in Adults, Health Literacy. The development and evaluation of educational materials considering the principles of health literacy was another prominent focus. The most studied public are users of the Sistema Único de Saúde with chronic diseases, especially people with systemic arterial hypertension or Diabetes mellitus; old people; professionals, health students and caregivers. Conclusion: Nursing has dedicated itself to researching health literacy in the Brazilian population, contributing to successful health education actions.